P0913 Bowel Urgency, an Independent Driver of Poor Quality of Life in IBD: A Romanian Tertiary Center Study - R E Saizu; A I Rotaru; D E Tantu; A M Dimitriu; A Les; L S Gheorghe; C Gheorghe (Journal of Crohn’s and Colitis, 2026)
Abstract Background Bowel urgency (BU) is a common and burdensome symptom in IBD, impacting quality of life even beyond periods of active inflammation. Functional sequelae may cause BU to persist in remission, yet it remains underrecognized in clinical practice. This study aimed to assess whether BU continues to impair quality of life during remission, supporting its relevance as an independent therapeutic target. Methods We conducted a prospective study of 82 IBD patients at Fundeni Clinical Institute, a national tertiary referral center. Bowel urgency was assessed using the recently developed Urgency Numeric Rating Scale (NRS), and quality of life with the Short IBDQ (SIBDQ) questionnaire. Clinical data included disease extent and activity, biomarkers, perianal disease, surgical history, and anorectal findings on endoscopy. Statistical analyses used Pearson or Spearman correlations and Mann–Whitney U tests, with p < 0.05 considered significant. Results The median age was 41 years (±12), with most patients having Crohn’s disease (61%), followed by Ulcerative Colitis (35%) and Unclassified Colitis (4%). Extended disease was frequent: ileocolonic involvement was most common in CD (45%), and pancolitis predominated in UC (54%). Most patients (95%) were receiving advanced therapies, mainly infliximab (42%), adalimumab (24%), and vedolizumab (18%). At evaluation, 81% were in clinical remission, 12% had mild disease, 6% moderate disease, and 1% a severe flare. Median fecal calprotectin was 122 µg/g (69% <250 µg/g), and median CRP was 1.43 mg/L (75% <5 mg/L), with neither marker correlating with urgency severity (p > 0.3). On the Urgency NRS, 20 patients (24%) reported a significant score ≥5. Ano-rectal lesions were absent in 73% and active perianal disease in 90%, and neither was associated with urgency (p > 0.2). Pearson correlation analyses showed that higher urgency scores were significantly associated with poorer quality-of-life outcomes across all SIBDQ items. Notable correlations were observed with fatigue (r = –0.53, p < 0.001), limitations in social engagements (p < 0.001), and restrictions in recreational or physical activities (r = –0.51, p < 0.01). Urgency was also significantly related to emotional impact, including depressive feelings (p < 0.001) and anger toward the disease (r = –0.29, p = 0.007). Conclusion Our findings demonstrate that bowel urgency remains a major determinant of impaired quality of life in IBD, independent of inflammatory activity or endoscopic/anorectal findings. The strong associations between urgency severity and multiple SIBDQ domains underscore its relevance as a distinct symptom burden. Routine evaluation of urgency should be integrated into patient assessment and may guide more personalized therapeutic strategies. References: 1. Dubinsky MC, Irving PM, Panaccione R, et al. Incorporating patient experience into drug development for ulcerative colitis: development of the Urgency Numeric Rating Scale, a patient-reported outcome measure to assess bowel urgency in adults. J Patient Rep Outcomes. 2022;6(1):31. Published 2022 Apr 1. doi:10.1186/s41687-022-00439-w 2. Dubinsky MC, Delbecque L, Hunter T, et al. Validation of the bowel urgency numeric rating scale in patients with Crohn’s disease: results from a mixed methods study. Qual Life Res. 2023;32(12):3403-3415. doi:10.1007/s11136-023-03494-y Conflict of interest: Dr. Saizu, Roxana Elena: No conflict of interest Rotaru, Alexandru Ionut: No conflict of interest Tantu, Diana Elena: No conflict of interest Dimitriu, Anca Mirela: No conflict of interest Les, Anda: No conflict of interest Gheorghe, Liana Simona: No conflict of interest Gheorghe, Cristian: No conflict of interest